KAJIAN YURIDIS TENTANG PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK KORBAN HUMAN TRAFFICKING - Ambarsari, Rr Ririen; Andiyansyah, Faniko Andiyansyah; Soewandi, Anugrah Adiputro (Jurnal Panorama Hukum, 2016)
Indonesia is among countries that are vulnerable to the sender and destination practice of human trafficking, especially for women and children. Therefore, this study aims to determine the forms of regulation of legal protection for women and children victims of Human Trafficking.This study found that the problem of trafficking stipulated in article 297 of the Kitab Undang-Undang Hukum Pidana as well as in Article 68 paragraph ( 2 ), Article 78; Article 83; Article 84; Article 85; and article 88 of Undang-Undang Perlindungan Anak.However, Kitab Undang-Undang Hukum Pidana contains substantial shortcomings in terms of protecting victims of crime, while Undang-Undang Perlindungan Anak also has drawbacks, among others: type of sanctions/criminal, old criminal, and criminal threats formulation system.Keywords: legal protection, trafficking, human trafficking, victims,